PHYSICOCHEMICAL AND SENSORY CHARACTERIZATION OF CREAM CRAKER BISCUITS MADE WITH CHICKPEA FLOUR - Cravo, Giullia Lorena da Silva Busch; dos Santos, Gabriel Calezani; Piccolo, Maria da Penha; Maradini Filho, Antonio Manoel (Seven Editora, 2025)
Chickpeas are a legume of the Fabaceae family, a source of proteins, lipids and carbohydrates, especially long-chain ones such as oligo and polysaccharides. Chickpea flour is considered nutritionally superior compared to refined wheat flour, showing itself to be an abundant source of protein. The use of mixed flours aims to partially replace wheat flour, aiming to improve the nutritional quality of food products and to meet the need of consumers for diversified products. The biscuits were made by mixing chickpea flour with wheat flour, in the proportions of 0%, 10%, 20%, 30% and 40% and other ingredients. Chickpea flour showed high levels of proteins, lipids and fibers, suggesting a high nutritional profile. The sensory analysis revealed that the color, aroma, and flavor attributes of the cookies were well evaluated, remaining within the hedonic preferences of "slightly liked" to "liked very much". Formulations with up to 40% added chickpea flour showed promising results in terms of texture and flavor, indicating a good receptivity on the part of consumers. The production of cream craker with chickpea flour can offer the food industry an opportunity to provide healthy and nutritious products. DOI: https://doi.org/10.56238/sevened2024.037-120